PERCEIVED EFFECTS OF FOOD PRICE INFLATION ON RURAL HOUSEHOLDS’ FOOD SECURITY SITUATION IN ENUGU STATE, NIGERIA - Q. ANUGWA, IFEOMA; UGWU, SAMUEL (Innovare Journal of Agricultural Sciences, 2022)
Objectives: This study examined the perceived effects of food price inflation on the food security status of rural farming households’ in Enugu state, Nigeria. Methods: The 18-item USDA household food security survey module was used in determining the food security status of the respondents. Mean scores were used to analyze the perceived causes and effects of food price inflation, respectively. Results: Majority of the households were food insecure, and the cost of production of major crops and prices of major stable foods had been on the increase for the 3 years (2016, 2015, and 2014) reviewed. The major cause of food price inflation was climate change while its major effects on household food insecurity were reduction in caloric intake, among others. Eating foods that are less preferred were the most frequently used coping strategy in cushioning the effects of food insecurity. Conclusion: The findings reveal how food price inflation affects rural farming households’ food security situation and thus assist the government and policy-makers to design and implement appropriate policy interventions.